In Situ Space Plasma Diagnostics With Finite Amplitude Active Electric Experiments: Non‐Linear Plasma Effects and Instrumental Performance of Mutual Impedance Experiments. Issue 12 (8th December 2022) - Bucciantini, L.; Henri, P.; Wattieaux, G.; Califano, F.; Vallières, X.; Randriamboarison, O.
Abstract: Mutual impedance (MI) experiments are a kind of plasma diagnostic techniques for the identification of the in situ plasma density and electron temperature. These plasma parameters are retrieved from MI spectra, obtained by perturbing the plasma using a set of electric emitting antennas and, simultaneously, retrieving using a set of electric receiving antennas the electric fluctuations generated in the plasma. Typical MI experiments suppose a linear plasma response to the electric excitation of the instrument. In the case of practical space applications, this assumption is often broken: low temperature plasmas, which are usually encountered in ionized planetary environments (e.g., RPC‐MIP instrument onboard the Rosetta mission, RPWI/MIME experiment onboard the JUICE mission), force toward significant perturbations of the plasma dielectric. In this context, we investigate MI experiments relaxing, for the first time, the assumption of linear plasma perturbations: we quantify the impact of large antenna emission amplitudes on the (a) plasma density and (b) electron temperature diagnostic performance of MI instruments. We use electrostatic 1D‐1 V full kinetic Vlasov‐Poisson numerical simulations. First, we simulate the electric oscillations generated in the plasma by MI experiments. Second, we use typical MI data analysis techniques to compute the MI diagnostic performance in function of the emission amplitude and of the emitting‐receiving antennas distance. We find the plasma density and electron temperature identification processes robust (i.e., relative errors below 5% and 20%, respectively) to large amplitude emissions for antenna emission amplitudes corresponding to electric‐to‐thermal energy ratios up to ϵ 0 E 2 / n 0 k B T e = 0.1 $\left({{\epsilon}}_{0}{E}^{2}\right)/\left({n}_{0}{k}_{B}{T}_{e}\right)=0.1$ . Key Points: The plasma response to large antenna emission amplitudes triggering non‐linear plasma perturbations is simulated Ion dynamics contributions to large amplitude propagating electric signals in the plasma are crucial and therefore should not be neglected Mutual impedance diagnostic performances are acceptable for emission amplitudes corresponding to electric‐to‐kinetic energy ratios up to 0.1